Developing Stories as Reading Materials for the Sixth Grade Students of SD N 7 Pedungan: Innovative Materials with the Insertion of Character Values - Norista, Elizabeth; Putu, Kerti Nitiasih; Luh Putu, Artini (Universitas Pendidikan Ganesha, 2013)
This study followed a research and development (R&D) model that aimed at developing stories as reading materials for the sixth grade students of SD N 7 pedungan with the insertion of character values. This study followed the R&D model proposed by Sugiyono that involves: analysing problem and potency, collecting data, designing product, validating design, revising design, developing product, evaluating product, field testing product, and revising product. The subjects of the study were the sixth grade students of SD N 7 Pedungan. The data were collected through questionaire, interview guide, observation sheet, expert judgment sheet and test. The collected data were analyzed qualitatively and quantitatively. The result of this study shows that: (1) The problems of the English teachers at SD N 7 Pedungan in teaching reading were; (a) the difficulties of finding interesting reading materials that are appropriate with the competencies standards, basic competencies, and the students? level of mastery; and (b) the absence of reading materials that integrated the character values; (2) the stories that were appropriate to be deveoped as reading materials for the sixth grade students of SD N 7 Pedungan were the stories with chronological plot, themes cover the sixteen character values, main character should be a child, and setting should be at school, in the characters? house or in the village. In addition, the stories should be interesting, appropriate with the competencies standards, basic competencies, and the students? level of mastery; (3) the development process of the products invloded: developing design, revising design, developing product, and evaluating product; (4) The strengths of the developed stories were: (a) the students love the stories and (b) the stories could increase the students? reading comprehension, integrate character values, and activate students to express their ideas. While the weakness of the developed stories was the students paid attention more on the picture than the text; and (5) The students give very positive attitude toward the implementation of the developed stories as reading materials. Keywords: R&D, reading material, character values, story